KAJIAN HUKUM PRA NIKAH DALAM MEMINIMALISASI TINGGINYA ANGKA PERCERAIAN DI KOTA MEDAN - Ginting, Dodi Efrata Fernando; Zarzani, T Riza; Anwar, Yohny; Sinaga, Hary Angga; Fauzan, Fauzan (Scenario (Seminar of Social Sciences Engineering and Humaniora); 2020, 2021)
Divorce data obtained from the Aga¬ma ministry, in 2011 there were 2,118,130 people who married and 324,527 people divorced. On average, there were 954 cases of divorce in 1 day. This high rate of divorce also occurs in Medan City. Within 1 day, as many as 70% of divorces occur due to wife's lawsuit against their husbands. Therefore it is necessary to provide an integrated, permanent and continuous treatment, namely in the form of prenuptial practical training. This pre-marital practical training must be designed, so that the content indicators can really fill in all the elements a couple needs before stepping into a marriage. This model was tested using the research and development method. Its particular target is to produce a practical training model for pre-marital education programs as an effort to minimize the high divorce rate, which can be used by the Ministry of Religion and the Office of Religious Affairs in Medan.